Land capability classification and management needs in Aravalli fringes of southern Haryana for sustainable land use planning - NAGDEV, RITU; MAHAPATRA, S K.; YADAV, R. P.; SINGH, S. K. (Journal of Soil and Water Conservation, 2017)
Land evaluation is an important criterion in assessing the suitability of land for the specified land use. Agricultural productivity in surroundings of Aravalli hills in Haryana is under threat due to undulating topography, soil characteristics, decline in ground water table and lack of proper management practices. Hence, a detailed soil survey was carried out in Shikohpur village of Gurgaon district, Haryana covering 934 ha area. Two major landform units have been identified in the area viz., Aravalli ridge and piedmont plains with aeolian influence. Six soils (Shikohpur A to F) have been identified and mapped into sixteen mapping units as phases of soil series. The soils have been evaluated based on potentiality and limitations for sustainable crop production. Shikohpur A and C soils cover 583.4 ha (62.4%) area and are rated as class III lands. They require organic manures and adequate doses of fertilizers for better crop production. Shikohpur B and D soils which occupy 185.5 ha (19.9%) area, are rated as class IV lands and require integrated nutrient management (INM) practices involving recommended doses of organic and inorganic fertilizers and sufficient irrigations for sustained productivity. Shikohpur E and F soils occur on rocky hill slopes of Aravallis covering 73.8 ha (7.9%) area belonging to class VI and VII lands which are basically non-agricultural lands. Soil and water conservation measures may be undertaken such as land leveling, afforestation, construction of engineering structures, besides ponds to store excess run-off water for its use in irrigation during dry spells.